Evaluation of Plasma Membrane Integrity of Sperm and Fertility of Post Thawed Frozen Semen of Black Bengal Goat - Ahmed, Imtiaz; Akhtar, Mahomudha; Akter, Tasmina; Akter Mohammad Yahia Khandoker, Mobarak (The Indian Journal of Animal Reproduction, 2026)
The study aimed to evaluate and compare the effectiveness of different freezing durations in combination with three  semen diluents (Triladyl, Andromed, and Tris-citrate) on sperm plasma membrane integrity and fertility of post-thawed  semen in Black Bengal goats. Data on frozen semen production and evaluation were collected over a period of six  months. Post-thawed semen samples were obtained according to the specified freezing times and diluents, and sperm  plasma membrane integrity was assessed using the Hypo-osmotic Swelling Test (HOST). In this study, 3 freezing times  (F1 = Freezing time 15 minutes, F2 = Freezing time 20 minutes, and F3 = Freezing time 25 minutes) were used in an ice  box filled with liquid nitrogen (LN) vapor. After freezing with 3 different freezing times and 3 diluters, F1 showed sperm  motility ranged from 20.3±1.33% to 53.7±.88%. A significant effect (p
Keywords: Black Bengal goat; Plasma membrane; Sperm; Fertility; Semen